2019
DOI: 10.30881/jogps.00026
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic simulation of cavitation bubbles formation in the axial valve separator influenced by degree of opening

Abstract: A stochastic modeling of the formation of cavitation bubbles on a specific example is proposed. In this case, the initial stage of hydrodynamic cavitation in the flow part of the axial valve, the separator, was studied. A distinctive feature of this regulating device is the external location of the locking organ. An expression for the differential distribution function of the number of bubbles according to the degree of valve opening is obtained. The model takes into account the design and operating parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 12 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…The performed experimental studies (Lebedev et al, 2017a,b) confirmed the possibility of reducing the intensity of hydrodynamic cavitation at its initial stage when using the modernized part of "separator-locking shell" of axial valve. In this case, a comparative analysis (Kapranova and Miadonye, 2019) of the obtained theoretical (Kapranova et al, 2016a(Kapranova et al, , 2017(Kapranova et al, , 2018aKapranova, 2018;Kapranova and Miadonye, 2019) and experimental (Lebedev et al, 2017a,b) results for the dependence of the differential distribution function of the number of bubbles f z (z) at the initial stage of hydrodynamic cavitation with a separator with round holes depending on the degree of their opening with using an external locking shell showed satisfactory convergence with a relative error not exceeding 13%. Note that the value of z is determined by the ratio of the given position z ′ for the movable shutter (external locking shell) along its axis to the conditional position L corresponding to the length of the perforated part of the separator.…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…The performed experimental studies (Lebedev et al, 2017a,b) confirmed the possibility of reducing the intensity of hydrodynamic cavitation at its initial stage when using the modernized part of "separator-locking shell" of axial valve. In this case, a comparative analysis (Kapranova and Miadonye, 2019) of the obtained theoretical (Kapranova et al, 2016a(Kapranova et al, , 2017(Kapranova et al, , 2018aKapranova, 2018;Kapranova and Miadonye, 2019) and experimental (Lebedev et al, 2017a,b) results for the dependence of the differential distribution function of the number of bubbles f z (z) at the initial stage of hydrodynamic cavitation with a separator with round holes depending on the degree of their opening with using an external locking shell showed satisfactory convergence with a relative error not exceeding 13%. Note that the value of z is determined by the ratio of the given position z ′ for the movable shutter (external locking shell) along its axis to the conditional position L corresponding to the length of the perforated part of the separator.…”
Section: Methodsmentioning
confidence: 83%
“…Earlier, the authors used the stochastic approach with the equilibrium representation of the states of the energetically closed macrosystem (Klimontovich, 2014;Tang et al, 2019) within the framework of the Ornstein-Uhlenbeck random process (Kapranova et al, 2016b) to form the model of this process the bubble formation process in the separator at the initial stage of hydrodynamic cavitation. The proposed stochastic models (Kapranova et al, 2016a(Kapranova et al, , 2017(Kapranova et al, , 2018aKapranova, 2018;Kapranova and Miadonye, 2019) allowed us to obtain differential distribution functions of the number of cavitation bubbles formed during the initial stage of the evolution of hydrodynamic cavitation, according to their size (Kapranova et al, 2016a(Kapranova et al, , 2017(Kapranova et al, , 2018a and the degree of opening of the axial valve (Arzumanov, 1971;Lebedev et al, 2017a,b). The performed experimental studies (Lebedev et al, 2017a,b) confirmed the possibility of reducing the intensity of hydrodynamic cavitation at its initial stage when using the modernized part of "separator-locking shell" of axial valve.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations